Moral Hazard in Electoral Teams - Gary W. Cox; Jon H. Fiva; Daniel M. Smith; Rune J. Sørensen (Center for Economic Studies and Ifo Institute (CESifo), 2020)
How do parties motivate candidates to exert effort in closed-list elections? If each candidate's primary goal is winning a seat, then those in safe and hopeless list positions have weak incentives to campaign. We present a model in which (i) candidates care about both legislative seats and the higher offices available when their party enters government; and (ii) parties commit to allocating higher offices monotonically with list rank. This model predicts that the volume and geo-diversity of candidates' campaign efforts will increase as their list rank improves. Using new data cover-ing Norwegian parliamentary candidates' use of mass and social media during the 2017 election, we find clear support for this prediction. As their list rank increases, candidates shift from intra-district to extra-district media exposure—which cannot help them win their own seats; but can improve their party's chance of entering government, and thus their own potential share of the spoils.
Keywords: D72; 330; party lists; cabinet promotion; Gamson's law; proportional representation; voter mobilization